Social Entrepreneurship: A Pakistani Perspective - Maqsood, Azra; Laghari, Javaid (JISR management and social sciences & economics, 2003)
Government, businesses, not for profits and local business communities and residents are all impacted by the globalization of the economy and those who live and work in all sectors and regions are the consumers who are also concerned about equity, the environment and sustainability. No one sector creates or can address the problems in isolation from another so new forms of analyzing the problems and responding to them with new sources of capital and cross sectional collaboration are needed. William Drayton, the founder of Ashoka: Innovators for the Public{1] is thought to have coined the term ‘social entrepreneur’ several decades ago. He is widely credited with creating the world’s first organization to promote the profession of social entrepreneurship. Over the last two decades, with the rise of the citizen sector, the popularity of the concept has exponentially increased. In Pakistan alone, Ashoka has since 1996 elected 18 fellows. These fellows work all across Pakistan from Swat to Quetta, to Hyderabad to Khairpur to pure urban populations like Karachi and Lahore in the fields of learning and education; environment; health; human rights; civic participation; economic development. Social Entrepreneurs like Nargis Latif (Gul Baho Trust), Roland De Souza (SHEHRD; Anwar Rashid (Orangi Pilot Project) and Zia Awan (Lawvers for Human Rights and Legal Aid) have already gained international acclaim for their work. These entrepreneurs are unique in the sense that their work has brought about a radical change in the existing social system within a short span of three years. This change is not limited to a neighborhood, but has an impact regionally, nationally and internationally, and all of this has been on a self sustained basis. A work of this magnitude requires community support, corporate and for profit collaboration and the government's patronage in the form of volunteer support, positive pressure groups, tax relief and multisectoral collaboration. Academia and researchers can fill the gap on research on this ‘new’ phenomenon of social development, while the government can extend support in publicizing and patronizing various social initiatives. Support in institutional strengthening and capacity building should be offered in collaboration with local and international NGOs to further nurture the work of the social entrepreneurs in Pakistan.